Quality assessment of extracted information from newspaper comment sections using natural language processing - Deb, Arnob; Islam, Maidul; Hossain, Sadab Sifar; Alam, Farjana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.